Морфологические обоснования эйрифагии овец - Игнатьев, Б.П. (Вестник зоологии, 1968)
The author studied comparatively the taste threshold in sheep, goats and cattle. It is established that sheep possess a higher threshold of percepting «bitter» and «sour». The threshold of percepting «salt» in the sheep is higher than in cattle, but lower than in goats and the threshold of percepting «sweet» is higher than in goats, but lower than in cattle. In the author's opinion, an explanation of this lies in topography and histological structure of taste nippels. In sheep the mushroom-like and roller-like nippels are covered with thick layer of keratinized cells of squamous epithelium and a number of taste boulbs in them is not more than 13. There is no leaf-like nippels in sheep. It may be assumed that euryphagy in sheep favoured their domestication and adaptation to human culture.